Agriculture Background Paper: Climate Bonds Standard & Certification Scheme - Wollenberg, Eva Karoline; Stirling, Claire; Havlík, Petr; Vuuren, Detlef P. van; Stehfest, Elke; Dittmer, Kyle M. (Climate Bonds Initiative, 2021)
The current trajectory of climate change, expected to lead to a global warming of 3.1-3.7°C by 2100, poses an enormous threat to the future of the world’s nations and economies. The aim of the Paris Agreement is to limit warming to a global average of no more than 2°C higher than pre-industrial levels by the end of the century, and ideally no more than 1.5°C. The effects of climate change and the risks associated even with a 2ºC rise are significant: rising sea levels, increased frequency and severity of hurricanes, droughts, wildfires and typhoons, and changes in agricultural patterns and yields. Meeting the 2ºC goal requires a dramatic reduction in global greenhouse gas emissions. At the same time, the world is entering an age of unprecedented urbanisation and related infrastructure development. Global infrastructure investment is expected to amount to USD 90 trillion over the next 15 years, more than the entire current infrastructure stock. To ensure sustainable development and avoid dangerous climate change, this infrastructure needs to be low-carbon and resilient to physical climate impacts, without compromising the economic growth needed to improve the livelihoods and wellbeing of the world’s poorer citizens. Ensuring that the infrastructure built is low-carbon raises the annual investment needs by 3–4%. Climate adaptation needs add another significant amount of investment, which is estimated at USD 280–500 billion per annum by 2050 for a 2ºC scenario.